PENGARUH MODEL COOPERATIVE SCRIPT BERBANTUAN MEDIA POSTER TERHADAP KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS IX UPTD SMP NEGERI 1 SEI DADAP TAHUN PELAJARAN 2024/2025 - Futi Hamdiyah Telaumbanua; Trisnawati Hutagalung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Cooperative Script learning model assisted by Poster Media on the ability to write procedural texts of class IX students of UPTD SMP Negeri 1 Sei Dadap. This type of research is quantitative research, experimental method using the Two Group Posttest research design. The population of this study was all class IX students of UPTD SMP Negeri 1 Sei Dadap totaling 128 people. In this study, the sampling technique was carried out by random sampling with samples, namely class IX-2 as the control class and class IX-1 as the experimental class. Data collection was carried out by interviews, observations (questionnaires) and tests. Data analysis techniques were carried out by normality tests, homogeneity tests and hypothesis tests. Based on the results of the normality test of the control and experimental classes, the data were normally distributed. The homogeneity test proves that the research sample is homogeneous. And the results of the hypothesis test show that t count> t table, which is 3.8371> 1.67065, so (Ho) is rejected and (H₁) is accepted. Thus, it can be concluded that there is a significant influence of the use of the Cooperative Script learning model assisted by poster media on the ability to write procedural texts of class IX students at UPTD SMP Negeri 1 Sei Dadap in the 2024/2025 academic year.